Human PD-L1 overexpression decreases xenogeneic human T-cell immune responses towards porcine kidneys - Schmalkuche, Katharina; Rother, Tamina; Besli, Sevval; Schwinzer, Reinhard; Blasczyk, Rainer; Petersen, Björn; Figueiredo, Constanca (Frontiers in Immunology, 2024)
Xenotransplantation offers a promising alternative to circumvent the lack of donated human organs available for transplantation. Different attempts to improve the survival of xenografts led to the generation of transgenic pigs expressing various combinations of human protective genes or knocked out for specific antigens. Currently, testing the efficiency of porcine organs carrying different genetic modifications in preventing xenogeneic immune responses completely relies on in vitro assays, humanized mouse models, or non-human primate transplantation models. However, these tests are often associated with major concerns due to reproducibility and generation of insufficient data as well as they raise ethical, logistical, and economic issues. In this study, we investigated the feasibility of specifically assessing the strength of human T-cell responses towards the kidneys of wild-type (WT) or transgenic pigs overexpressing human programmed death-1 ligand 1 (hPD-L1) during ex vivo kidney perfusion (EVKP). Human T cells were shown to adhere to the endothelium and transmigrate into WT and hPD-L1 kidneys. However, transcript levels of TNF-a and IFN-y as well as cytotoxic molecules such as granzyme B and perforin secreted by human T cells were significantly decreased in the tissue of hPD-L1 kidneys in comparison to WT kidneys. These results were confirmed via in vitro assays using renal endothelial cells (ECs) isolated from WT and hPD-L1 transgenic pigs. Both CD4+ and CD8+ T cells showed significantly lower proliferation rates after exposure to hPD-L1 porcine renal ECs in comparison to WT ECs. In addition, the secretion of pro-inflammatory cytokines was significantly reduced in cultures using hPD-L1 ECs in comparison to WT ECs. Remarkably, hPD-L1 EC survival was significantly increased in cytotoxic assays. This study demonstrates the feasibility of evaluating the human response of specific immune subsets such as human T cells towards the whole xenograft during EVKP. This may represent a robust strategy to assess the potency of different genetic modifications to prevent xenogeneic immune responses and thereby predict the risk of immune rejection of new genetically engineered xenografts.